2003
DOI: 10.1097/01.ccm.0000070446.84095.f4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing for electrical defibrillation after prolonged untreated ventricular fibrillation

Abstract: Improved outcome after prolonged untreated ventricular fibrillation may result from strategies that provide chest compression before attempting defibrillation and avoid early and repetitive defibrillation attempts. The amplitude and frequency characteristics of the ventricular fibrillation waveform could help identify the optimal timing for attempting electrical defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 31 publications
(50 reference statements)
1
39
0
4
Order By: Relevance
“…In a dog model, a brief CPR before defibrillation improved the resuscitation outcome from prolonged VF [15]. Kolarova et al [16] showed that the rate of restored spontaneous circulation increased in proportion to the duration of CPR before defibrillation. In this study, less than 2 minutes of CPR before defibrillation did not improve the rate of restored spontaneous circulation [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a dog model, a brief CPR before defibrillation improved the resuscitation outcome from prolonged VF [15]. Kolarova et al [16] showed that the rate of restored spontaneous circulation increased in proportion to the duration of CPR before defibrillation. In this study, less than 2 minutes of CPR before defibrillation did not improve the rate of restored spontaneous circulation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies reported that CPR before defibrillation had various benefits [14][15][16]. In swine with 8 minutes of untreated VF, CPR for 90 seconds followed by defibrillation shock resulted in physiological benefits and a superior response to initial defibrillation in comparison with immediate defibrillation [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also demonstrated by a study by Achleitner et al 21 in which VF mean frequency (CF correspondent) was shown to correlate significantly with the coronary perfusion pressure during compressions in pigs, whereas VF mean amplitude (ENRG correspondent) demonstrated no such correlation. Finally, Kolareva et al 22 recently concluded that improved outcome after prolonged untreated VF in rats may result from strategies that provide chest compressions before defibrillation and avoid early and repetitive defibrillation attempts. In their model, 6 minutes of CPR gave the best ROSC and survival results, and they found a progressive increase in a variant of AMSA and mean amplitude (ENRG correspondent) with a compression duration that correlated significantly with the chance of ROSC.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches are being developed to optimize the effectiveness of electrical defibrillation by identifying the proper timing for shock delivery and by using safer and more effective defibrillation waveforms. (24,25) …”
Section: Decreased Left Ventricular Compliancementioning
confidence: 99%